Posttraumatic Subfibular Ossicle Formation in Children: Experience in a Single Primary Care Unit. Issue 9 (October 2018) - Lee, Dong Yeon; Lee, Doo Jae; Kim, Dong Han; Shin, Hyuck Soo; Jung, Whan Ik
Abstract : Background: Although subfibular ossicles have been linked to various clinical problems, whether its origin is congenital or traumatic remains unclear. The objectives of this study were to determine the incidence of subfibular ossicle formation after ankle inversion in children. Methods: Among 896 pediatric patients who visited a single primary care unit after foot and ankle trauma, 593 patients sustaining ankle inversion injury were included in this study. For each pediatric patient, physical examination and radiographic examination were performed. The incidence of subfibular ossicle was evaluated based on initial radiographic examination. To analyze the incidence of unprecedented subfibular ossicle formation after ankle inversion injury, radiographs of 188 patients who were followed up for >6 months were evaluated according to the grade of initial injury. Results: At initial visit, 1.0% of examined ankles (12 from 1186 ankles) showed well-corticated subfibular ossicle not related to initial injuries. Overall incidence of subfibular ossicle at final follow-up after ankle inversion injury was 39.4% (74/188). Incidence of subfibular ossicle at final follow-up was associated with initial injury grade. As for the morphology of ossicle, 93.2% (55/59) of cases with wafer bone fragment at the time of initial injury became oval or round-shaped subfibular ossicle at final radiograph. Conclusions: The chance of ossicle formation after ankle inversion injury was substantially high in pediatric population. On the basis of the findings of our study, we carefully suggest that majority, if not all, of subfibular ossicles would be posttraumatic in pediatric period. Level of Evidence: Level IV—case series.